2023
DOI: 10.1021/acsfoodscitech.3c00129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Particle Size, Solvent Type, and Extraction Temperature on the Extraction of Crude Cannabis Oil, Cannabinoids, and Terpenes

Abstract: Optimized medicinal plant processing and extraction can improve extract yield and efficiency for valued secondary metabolites while reducing operation costs. This study investigated the effects of the particle size [coarse (2–4 mm), medium (0.5–2 mm), fine (0.25–0.5 mm)], solvents (ethanol, butanol, hexane), and extraction temperature (−20 °C, 4 °C, room temperature) on extracted crude cannabis oil yield and cannabinoid/terpene concentrations using a full factorial design. Results indicate that finer particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 62 publications
(117 reference statements)
1
0
0
Order By: Relevance
“…Furthermore, the findings correspond to De Vita et al [21], who found that CBD and THC concentrations increased with increasing ethanol concentration. Therefore, this finding is consistent with other reports [21,22] that ethanol is preferred for extraction of CBD over nonpolar organic solvents.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the findings correspond to De Vita et al [21], who found that CBD and THC concentrations increased with increasing ethanol concentration. Therefore, this finding is consistent with other reports [21,22] that ethanol is preferred for extraction of CBD over nonpolar organic solvents.…”
Section: Discussionsupporting
confidence: 93%